Rendszerváltó évek. Zaklatott ősz 1990 . Years of Transition in Hungary. A Turbulent Autumn 1990 (MTV - Hungarian Television, 1997)
Television program about the political and social issues of the transition from "socialism" to multi-party democracy in Hungary.